Auditory brainstem response in neonates: influence of gender and weight/gestational age ratio - Rosanna M. Giaffredo Angrisani; Ana Paula D. Bautzer; Carla Gentile Matas; Marisa Frasson de Azevedo (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To investigate the influence of gender and weight/gestational age ratio on the Auditory Brainstem Response (ABR) in preterm (PT) and term (T) newborns. METHODS: 176 newborns were evaluated by ABR; 88 were preterm infants - 44 females (22 small and 22 appropriate for gestational age) and 44 males (22 small and 22 appropriate for gestational age). The preterm infants were compared to 88 term infants - 44 females (22 small and 22 appropriate for gestational age) and 44 males (22 small and 22 appropriate for gestational age). All newborns had bilateral presence of transient otoacoustic emissions and type A tympanometry. RESULTS: No interaural differences were found. ABR response did not differentiate newborns regarding weight/gestational age in males and females. Term newborn females showed statistically shorter absolute latencies (except on wave I) than males. This finding did not occur in preterm infants, who had longer latencies than term newborns, regardless of gender. CONCLUSIONS: Gender and gestational age influence term infants' ABR, with lower responses in females. The weight/gestational age ratio did not influence ABR response in either groups.